A multicriteria approach for assessing agricultural productivity. (2017) - Tarnanidis, Theodore; Papathanasiou, Jason; Vlachopoulou, Maro; Manos, Basil; Kalioropoulou, Anna
This paper investigates the agricultural productivity in rural areas based on productivity indicators of agricultural resources, like the gross return produced per agricultural land in these areas, by using the decision-making approach PROMETHEE II. This approach was applied for the assessment of productivity and for the ranking of the seven prefectures of the region of Central Macedonia in Northern Greece with data for the period from 2013 to 2014. The results revealed that the prefecture of Pella surpasses in productivity the remaining six, followed by Imathia and Chalkidiki. Finally, the validity of the specific ranking results is discussed and recommendations are given for the improvement of regional performance and productivity.